Analysis of Electrical Energy Consumption in Office Buildings of the Institute Technology of Sumatra in Energy Conservation and Efficiency Efforts - Naimah, Khoirun; Arirohman, Ilham Dwi; Zen, Muhammad Rizky; Wicaksono, Rihardian Maulana; Soelami, F.X. Nugroho; Rahmatullah, Abri; Purba, Leonardo D.; Gaol, Javeni Eysama L. (DPTE FT UNY, 2023)
Electrical energy is one of the basic human needs in carrying out various activities or daily activities, especially in office buildings such as office buildings of state higher education institutions, namely the Sumatra Institute of Technology (ITERA). Office buildings are the third highest consumer of electrical energy after shopping centers and hotels. The high demand for electrical energy requires the user sector to make efficiency in energy use. Before making efficiency, it is necessary to know the profile of electrical energy consumption including energy consumption intensity (ECI) and significant energy users. Therefore, in this study, an analysis of electrical energy consumption in each ITERA office building was carried out, through observation and interviews according to SNI / ISO 50002: 2018 energy audit procedures. The results obtained show that the total energy use of the 6 largest buildings (A, B, C, D, E, and F) in May 2023 is 144768 kWh and from the calculation of the ECI value is in the very efficient category (7.44 kWh/m2/month). From 6 existing buildings, there are 3 buildings that are very efficient, 1 building is efficient, and 2 buildings are quite efficient. Then, significant energy users were found by 83% in building C AC. Recommendations for saving energy in the effort of energy conservation and efficiency that can be done include, making changes in habits / patterns of use of electrical energy user equipment, especially in air conditioners and dispensers, so as to save electricity 2-21%, and retrofitting refrigerant AC types of split ducts and cassettes that still use R-22 with MC-22 which can save electricity 15-25%.